Reliability and Agreement of the 10-Repetition Maximum Test in Breast Cancer Survivors - Santos, Wanderson Divino Nilo dos; Siqueira, Gabriel Dutra de Jesus; Martins, Wagner Rodrigues; Vieira, Amilton; Schincaglia, Raquel Machado; Gentil, Paulo; Vieira, Carlos Alexandre (Frontiers in Oncology, 2019)
The aim of this study was to evaluate the reliability and agreement between the test and retest of the 10-repetition maximum (10-RM) test for leg press and bench press in breast cancer survivors (BCS). Thirty-one BCS participated in this study, age 54.87 ± 5.7 years. All performed 10-RM tests and retests for the leg press 45° and the bench press. For reliability analyses, an intraclass coefficient correlation (ICC) and coefficient of variation (CV) were performed. The limits of agreement were calculated using a Bland-Altman plot with 95% CIs. For absolute and relative error of measurement, we used standard error of measurement and minimally detectable change. The result showed a high reliability for the bench press and leg press; ICC of 0.94 and 0.98, respectively. CV was <10% for both exercises. The systematic error were 1.5 kg (10%) and 6.1 (8%) for the bench press and leg press, respectively. The standard errors of measurements were 0.96 kg (6.08%) and 4.11 kg (5.27%) for the bench press and leg press, respectively. The minimally detectable changes were 2.72 kg (17.20%) and 5.62 kg (7.21%) for the bench press and leg press, respectively. In breast cancer survivors, the muscular strength measurement for the 10-RM test showed a high to very high rate of reliability and agreement, with acceptable error of measurement.